A Bibliometric Analysis of Cryptocurrency and Blockchain - Yona, Yona Sri Idris; Shidqi, Shidqi Rijq Al-Thelayaty Marls; Lemon, Riski Alifiawan (Westscience Press, 2024)
Cryptocurrency and blockchain technology have changed the financial environment, giving decentralized and secure alternatives to existing institutions. Cryptocurrencies, like Bitcoin and Ethereum, leverage blockchain as a distributed ledger to record transactions openly and immutably. The blockchain's decentralized structure maintains trust and removes the need for middlemen, boosting efficiency and decreasing fraud risks. Cryptocurrencies allow borderless and fast transactions, encouraging financial inclusion internationally. Despite their transformational potential, problems such as regulatory uncertainty and environmental concerns surround cryptocurrencies. The continued advancement of this revolutionary technology has spurred questions about its long-term implications on finance, government, and beyond. As the world continues to explore the huge potential of cryptocurrencies and blockchain, their disruptive effect on numerous sectors remains a major topic of attention and controversy.